Rancang Bangun Aplikasi Pembelajaran Dengan Metode Drill And Ppractice Berbasis Android Di SMA AL-FALAH Ketintang - Pratama, Ardo Yoga; hariadi, bambang; nurcahyawati, vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
This research is motivated by the problems of the activities of intensive exercises that applied to students of class XII, considering the student will face national exam (UNAS). This activity is done manually using paper, and made within the last 3 months XII class teaching and learning process. In the course of intensive exercises having some problems such as: the lack of time the application of intensive activity exercises, the use of the manual system causes the resulting information is still static and not give actual information, and lack the information needed to monitor the development activities of teacher-intensive exercises. To overcome some of these obstacles, constructed a plan to build learning applications with drill and practice-based methods android, or the so-called D-SMART. D-SMART has a function Deliver exercises, Notification of new matter. In addition to overcoming determine the achievement of performance is D-SMART method produces an output in the form of graphs and details. D-SMART can help the implementation of intensive exercises which have reduced hours class XII student learning. Time intensive exercises with drill and practice methods are becoming increasingly enhanced, the start of class X in order to get the best value when students face national exam (UNAS)